2009
DOI: 10.3164/jcbn.sr09-58
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of NSAID-Induced Small Intestinal Mucosal Injury: Prophylactic Potential of Lansoprazole

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs), which are used for the treatment of several inflammatory disorders including rheumatoid arthritis, are well known to cause gastroduodenal mucosal lesions as an adverse effect. Recently, the serious problem of NSAID-induced small intestinal damage has become a topic of great interest to gastroenterologists, since capsule endoscopy and double-balloon enteroscopy are available for the detection of small intestinal lesions. Such lesions have been of great concern in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 50 publications
1
32
0
2
Order By: Relevance
“…ibobrufen, paracetamol, indomethacin etc. for the recovery of pain and inflammation, ultimately lead to severe side effects like ulcer in gastro-intestinal tract [35][36][37]. Interestingly, C. procera is one the plant that contains several phytochemicals and few of these have already been documented for anti-inflammatory properties [9,[38][39], which supported the present computational prediction.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…ibobrufen, paracetamol, indomethacin etc. for the recovery of pain and inflammation, ultimately lead to severe side effects like ulcer in gastro-intestinal tract [35][36][37]. Interestingly, C. procera is one the plant that contains several phytochemicals and few of these have already been documented for anti-inflammatory properties [9,[38][39], which supported the present computational prediction.…”
Section: Resultssupporting
confidence: 74%
“…It leads to internal and external inflammation in tissues, organs etc. There are well established anti-inflammatory synthetic drugs, which help as pain killer as well as recovery of swelling in tissues however, may cause side effect like ulcer in gastrointestinal tract [33][34][35][36][37]. Moreover, aqueous flower extract of C. procera has been documented to arrest pain, fever and inflammation [38][39] while ethanolic extract of root bark showed anti-inflammatory properties without any side effect [9,40].…”
Section: Introductionmentioning
confidence: 99%
“…Kuroda et al (2006) first reported that LPZ had an inhibitory effect on IND-induced small intestinal lesions in rats and suggested that LPZ prevented intestinal lesions by anti-inflammatory and antioxidant mechanisms, because LPZ inhibited INDinduced increase of myeloperoxidase activity and thiobarbituric acid-reactive substance in the intestinal mucosa. Higuchi et al (2009) and Yoda et al (2010) reported that LPZ, but not OPZ, prevented IND-induced intestinal lesions in rats and suggested that LPZ protected the intestinal mucosa by up-regulation of hemoxygenase-1 production in the mucosa. We reported previously that LPZ protects the gastric mucosa by a mechanism independent from its antisecretory action, and both CSSN and NO are involved in the protective mechanism of LPZ on the gastric mucosa (Murakami et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous PGE (2) promotes the healing of small intestinal lesions [42,43]. Lansoprazole prevents indomethacin-induced small intestinal ulceration [44,45]. However opposite results have been reported later on.…”
Section: Prevention and Therapy Of Non-steroidal Antiinflammatory Drumentioning
confidence: 87%